Report 8: How to Build a Merchandise Knowledge Test - Chartier, Roger (Relations industrielles / Industrial Relations, 1953)
The article briefly reviews "Report 8: How to Build a Merchandise Knowledge Test," by Josephine S. Welch and C. Harold Stone. July 1951 (21 pages).